Mortality and Disability Due to Japanese Encephalitis in Elderly Adults: Evidence From an Adult Tertiary Care Center in West China - Xiong, Weixi; Lu, Lu; Xiao, Yingfeng; Li, Jinmei; Zhou, Dong (Frontiers in Neurology, 2019)
Japanese encephalitis (JE) is the most important cause of viral encephalitis in Asia, with most cases seen in children <15 years. Recently, cases of JE in people aged >50 years have been increasingly reported, but the clinical presentation in these cases is largely unknown. We report here the first case series of elderly JE patients from an adult tertiary hospital in West China. Medical records of laboratory-confirmed JE patients diagnosed from January 2011 to September 2018 were reviewed retrospectively. Patients were grouped into the elderly (patients > 50 years old) and control groups (patients aged 14–50 years). Data regarding demographics, clinical features, and outcome at discharge were collected. Telephonic follow-up was performed with the survivors in November 2018. Of the 50 patients with laboratory-confirmed JE, 11 were aged >50 years. In the elderly group, all patients had high fever and altered sensorium, and six had symptomatic seizures. Though the key symptoms as well as the cerebrospinal fluid and neuroimaging findings were similar in both groups, the worst Glasgow coma scale score was lower in the elderly group (6.14 ± 2.27 vs. 10.54 ± 3.37, p = 0.001). Compared to the control group, the incidence of acute secondary complications, including respiratory failure requiring mechanical ventilation or tracheotomy (81.82%), hypoalbuminemia (100%), thrombocytopenia (100%), deep venous thrombosis (63.64%), septicemia (36.36%), and upper gastrointestinal bleeding (27.27%) was higher in the elderly. The median modified Rankin scale (mRS) score at discharge was lower in the elderly group than in the control group (5 vs. 3, p = 0.017), with four and two cases of death, respectively. During the average 18-month follow-up, the median mRS score was 5 in the elderly and 2 in the control group (p = 0.001). Patients >50 years old accounted for 22% of JE cases diagnosed in a tertiary adult center, with high mortality rate and long-term disability compared to younger patients. Though no particular findings were found regarding clinical features and investigations in patients >50 years, most needed intensive care. In the future, it is imperative to recognize the importance of JE in adults and to reconsider the vaccination strategy in adult residents of endemic areas, especially for those over 50 years.